Spinal epidural hematoma without significant trauma in children: two case reports and review of the literature - Audrey Carlhan-Ledermann; Bernard Laubscher; Maja Steinlin; Christian T. Ulrich; Rajeev Kumar Verma; Mattia Rizzi; Rodolfo Maduri; Sebastian Grunt (BMC, 2020)
Abstract Background Spinal epidural hematoma without significant trauma is a rare condition with potentially severe outcome. This case report and systematic review of the literature illustrates the clinical presentation, risk factors, evaluation, treatment and outcomes of spinal epidural hematoma without significant trauma in children. Case presentation We report one case of a 7-year-old girl who developed a neck pain after minor cervical sprain. MRI showed a right posterior epidural hematoma extending from C2/3 to T1. The hematoma was surgically evacuated, and the histopathology showed an arteriovenous malformation. Postoperative MRI showed complete evacuation of the hematoma and no residual vascular malformation. We report a second ASE with idiopathic spinal epidural hematoma of a 4½-year-old boy presenting with neck pain. MRI showed a right-sided latero-posterior subacute spinal epidural hematoma at C3-C5. Owing to the absence of any neurological deficit, the patient was treated conservatively. MRI at 3 months showed complete resolution of the hematoma. Conclusions Spinal epidural hematoma without significant trauma in children is a rare condition. It may present with unspecific symptoms. Screening for bleeding diathesis is warranted and neuroradiologic follow-up is essential to rule out vascular malformation. Whereas most children have a favorable outcome, some do not recover, and neurological follow-up is required.